1994
DOI: 10.1161/01.hyp.24.1.16
|View full text |Cite
|
Sign up to set email alerts
|

In vitro perfusion studies of human resistance artery function in essential hypertension.

Abstract: To simulate in vivo conditions as closely as possible to in vitro conditions, we examined the morphological and functional characteristics of isolated human subcutaneous small arteries from 17 essential hypertensive patients and 14 normotensive control subjects using a perfusion myograph. Vessel segments were cannulated and exposed to conditions of constant flow and pressure. The ratio of media thickness to lumen diameter in arteries from hypertensive patients increased significantly. With the endothelium inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…In established essential hypertension there is evidence of an increased pressor response to vasoconstrictors 34 ; however, sensitivity to vasoconstrictors seems to be unchanged. 35 Eliasson et al 36 found borderline hypertension to be associated with enhanced cardiovascular reactivity revealed by MST but not by orthostatic testing or cold pressor test in their comparison of groups of established and borderline hypertensives with normotensives. Jern 22 found a correlation between stress-induced increase in forearm blood flow and increased forearm glucose extraction during MST in nonobese normotensive men.…”
Section: Discussionmentioning
confidence: 97%
“…In established essential hypertension there is evidence of an increased pressor response to vasoconstrictors 34 ; however, sensitivity to vasoconstrictors seems to be unchanged. 35 Eliasson et al 36 found borderline hypertension to be associated with enhanced cardiovascular reactivity revealed by MST but not by orthostatic testing or cold pressor test in their comparison of groups of established and borderline hypertensives with normotensives. Jern 22 found a correlation between stress-induced increase in forearm blood flow and increased forearm glucose extraction during MST in nonobese normotensive men.…”
Section: Discussionmentioning
confidence: 97%
“…23 Small arteries 65 m to 230 m were isolated and carefully cleaned under a dissecting microscope. Vessels were transferred to an arteriograph bath chamber (Living Systems Instruments, Burlington, Vt), 23 cannulated, 24,25 and examined as described previously. 15 …”
Section: Pressure Arteriographymentioning
confidence: 99%
“…medium-sized conduit arteries 8 and in resistance arteries. 9,10 Nonhypertensive patients with symptoms of angina pectoris, but with normal coronary angiograms, have decreased flow-mediated dilatation (FMD) in the brachial artery during reactive hyperaemia, 11 as well as increased minimal forearm vascular resistance (FVR), 12 suggesting parallel vascular dysfunction in the coronary and peripheral vasculature. This parallel vascular dysfunction has also been identified by Leschke et al, 13 who found increased minimal FVR in hypertensive patients with reduced MFR.…”
Section: Introductionmentioning
confidence: 99%